2020
DOI: 10.1098/rsta.2019.0482
|View full text |Cite
|
Sign up to set email alerts
|

The rings and small moons of Uranus and Neptune

Abstract: All four giant planets are encircled by distinctive systems of rings and small, inner satellites. These all reside within or near their central planet's Roche limit, the rough boundary within which bodies held together by self-gravity will be disrupted by tidal forces. However, the similarities of the four ring-moon systems end here; in most other regards, they are remarkably diverse. We study these systems for three key reasons: (1) for the information they reveal about the properties, history and ongoing evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The gray region indicates where formation of massive moons may be limited by disk migration, while a larger Hill radius maximizes primordial and new material to contribute to ring formation. , 2020Wakeford & Dalba 2020). The detailed data available for local giant planet systems must necessarily be balanced by the statistical knowledge that will be gained through the discovery of exomoons and exorings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gray region indicates where formation of massive moons may be limited by disk migration, while a larger Hill radius maximizes primordial and new material to contribute to ring formation. , 2020Wakeford & Dalba 2020). The detailed data available for local giant planet systems must necessarily be balanced by the statistical knowledge that will be gained through the discovery of exomoons and exorings.…”
Section: Discussionmentioning
confidence: 99%
“…A distinctive common feature of the giant planets within the solar system is the presence of ring systems orbiting the planet. Rings systems have been detected and studied extensively for each of Jupiter (Showalter et al 1987;Porco et al 2003), Saturn (Pollack 1975;Porco et al 2005), Uranus (Elliot et al 1977;Tyler et al 1986), and Neptune (Lane et al 1989;Showalter 2020). In particular, the prominent rings of Saturn have been the source of numerous investigations with regards to their formation (Goldreich & Tremaine 1978a;Charnoz et al 2009) and dynamics (Goldreich & Tremaine 1978b;Bridges et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery (Elliot et al 1977), scientists have puzzled over how the Uranian rings maintain their narrow and noncircular structures (French et al 1991) but sometimes also show striking changes (de Pater et al 2007). Voyager 2 and Earth-based observations have revealed that Uranus hosts a system of dense, narrow rings lacking meaningful spacing, diverse broad and finely structured dusty rings, and the most tightly packed system of small moons in our solar system (Figure 7; Nicholson et al 2018;Showalter 2020). This "dynamically full" system is known to be unstable and is brimming with interesting interactions and dynamics, including overlapping resonant interactions between multiple moons (French et al 2015).…”
Section: Ring Sciencementioning
confidence: 99%
“…The small regular moons comprising the Portia group in the Uranian system represent the most densely-packed set of satellites known, with semimajor axis separations of 3% on average (Showalter 2020); as such, the system is predicted to be chaotic, with collisions occurring on 10 5 -to 10 7 -year timescales (Duncan & Lissauer 1997;French & Showalter 2012). Indeed, the faint dusty ν ring, situated between the orbits of Portia and Rosalind, has been proposed to be the remnant of such a collision (Showalter 2020). Due in part to this small orbital spacing, the Uranian satellites likely affect each other's surface properties via dust transport in the circumplanetary environment.…”
Section: Introductionmentioning
confidence: 99%